Conformity and Interpersonal Drivers of Adolescent Bandwagon Behavior: Konformitas dan Faktor Pendorong Interpersonal dalam Perilaku Ikut-ikutan Remaja - Zaidan Aufi Romadhoni; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The bandwagon effect describes individuals’ tendency to follow behaviors or trends adopted by others. Specific Background: Among students, peer interaction frequently shapes participation in popular trends within school environments. Knowledge Gap: Limited qualitative research explores adolescents’ lived experiences in understanding how bandwagon behavior forms. Aims: This study investigates the manifestation of bandwagon phenomena among high school students. Results: Using a qualitative phenomenological approach at SMA Muhammadiyah 2 Sidoarjo with three participants, data from interviews revealed that conformity and interpersonal factors played stronger roles in trend participation than status motives. Students often followed trends without prior evaluation and reported mixed outcomes, including positive and negative experiences. Novelty: This study offers phenomenological insight into students’ subjective perspectives by examining conformity, interpersonal dynamics, and status orientation within bandwagon behavior. Implications: The findings provide contextual understanding for educators and psychologists to develop awareness and guidance strategies related to adolescent social behavior in educational settings. Highlights: Peer Group Alignment Encourages Unconsidered Trend Participation Among Students. Social Interaction Processes Shape Decision-Making Patterns Related to Popular Activities. Participation in Popular Trends Produces Both Beneficial and Adverse Student Experiences. Keywords: Bandwagon Phenomenon, Student Social Behavior, Trend Adoption, Phenomenological Psychology, Peer Dynamics